Factors Associated With Cadre Participation in Posyandu Activities in the Meuraxa Area of Banda Aceh - Aspiati (Jurnal EduHealth, 2022)
Cadres are members of the local community who are elected, reviewed by the community and work voluntarily. The role of cadres in improving the level of public health is very much needed, one of which is in efforts to reduce infant and toddler mortality rates, and stabilize birth rates so that happy and prosperous small families can be created with family planning programs that can be promoted by cadres to the community. The research aims to assess factors related to cadre participation in posyandu activities in Meuraxa District, Banda Aceh City. This research uses an analytical survey method with a cross sectional approach. The population in the study were all Posyandu cadres in Meuraxa District, Banda Aceh City, totaling 30 people. which consists of 6 Posyandu and each Posyandu has 5 cadres. The results show that there is a significant relationship between knowledge, cadre needs, appreciation, the role of community leaders and the role of health workers where the p-value of these five variables is 0.000 with the participation of posyandu cadres in Meuraxa District, Banda Aceh City. The health center and the Medan city health office can develop policies that can increase cadre participation in posyandu activities, such as maximizing cadre refreshment, providing the latest information about health and adding nutritional health workers to posyandu activities. the role of community leaders and the role of health workers where the p-value of these five variables is 0.000 with the participation of posyandu cadres in Meuraxa District, Banda Aceh City. The health center and the Medan city health office can develop policies that can increase cadre participation in posyandu activities, such as maximizing cadre refreshment, providing the latest information about health and adding nutritional health workers to posyandu activities. the role of community leaders and the role of health workers where the p-value of these five variables is 0.000 with the participation of posyandu cadres in Meuraxa District, Banda Aceh City.